The Proteolytic Cleavage of Therapeutic Monoclonal Antibody Hinge Region: More Than a Matter of Subclass - Deveuve, Quentin; Lajoie, Laurie; Barrault, Benjamin; Thibault, Gilles (Frontiers in Immunology, 2020)
The hinge region of immunoglobulin G (IgG) is involved in C1q and FcRIIIa-expressing natural killer (NK) cell recruitment. Both heavy chains (HCs) of the hinge region can be cleaved sequentially by several proteases of the tumor/inflammatory/infectious microenvironment, including matrix metalloproteinase 12 (MMP12) or immunoglobulin-degrading enzyme from Streptococcus pyogenes (IdeS), impairing Fc-mediated functions. The cleavage of therapeutic monoclonal antibodies (TmAbs), which are based on a human IgG1, IgG2 or IgG4 structure, has been poorly investigated, although it may represent an escape mechanism to these treatments. Therefore, we used non-reducing SDS-PAGE to compare the cleavage kinetics of five IgG1 TmAbs (trastuzumab, rituximab, cetuximab, infliximab, ipilimumab), one IgG2 TmAb (panitumumab) and two IgG4 TmAbs (nivolumab and pembrolizumab) by MMP12 and IdeS, which were found to cleave the first and second HCs with different kinetics. Panitumumab was more protease-resistant than IgG1 and IgG4 TmAbs. The latter were usually more protease-sensitive, whereas IgG1 TmAbs were usually cleaved with intermediate kinetics. However, we observed intra-subclass variability among IgG4 and IgG1 TmAbs. Nivolumab and pembrolizumab were cleaved similarly by MMP12, whereas pembrolizumab was more IdeS-resistant. Ipilimumab was more IdeS-sensitive and MMP12-resistant than the other IgG1 TmAbs, regardless of G1m allotype. In addition the Fc fragment of IgG1 TmAbs were highly resistant to cleavage by MMP12, whereas their cleavage kinetic by IdeS was very similar to that observed with the intact forms (excluding ipilimumab). Importantly, the cleavage kinetic of ipilimumab Fc fragment by IdeS was superimposable to that of trastuzumab, cetuximab and infliximab Fc fragment, showing that the variability observed for intact ipilimumab is unrelated to its Fc portion. We propose that the variability in the cleavage sensitivity/resistance balance among TmAbs of IgG1 and IgG4 subclasses results partially, from TmAb characteristics related to and/or located in the Fab region. Finally, with ELISA and flow cytometry, we observed that a single cleavage of IgG1 TmAbs greatly decreased their affinity for FcRIIIa and C1q and their ability to induce FcRIIIa-dependent functional responses of NK cells. Overall, our results indicate that the cleavage of the hinge region should be considered with TmAbs treatment and in the development of new molecules.